Adoption of raised bed technology in some selected locations of Rajshahi District of Bangladesh (Bangladesh Journal of Agricultural Research, 2016)
The study evaluated the adoption and farmers practice of raised bed technology at farm level since the close of the Soil Management Collaborative Research Support Program (SMCRSP) through a follow-up survey conducted at Durgapur Upazila of Rajshahi district. Data for the study were collected from 195 adopters and 65 non-adopters through a pre-tested interview schedule during May, 2011. The survey findings showed that the raised bed technology had a strong demonstration effect and were adopted well (56%) by the respondent farmers. The probability of adopting this technology was significantly influenced by extension contact, societal membership, and the number of male member in the household. Due to lack of machine, most farmers prepared raised bed by hand (82.7%) without maintaining recommended bed size. The most cultivated crops on bed were wheat (cultivated by 97.95% farmers) maize (27.69%) onion (16.41%) and mungbean (12.31%). Respondent farmers mentioned various positive benefits of bed technology and willing to continue this practice in future with increased area of land. This immerging technology increased cop productivity and farmers income to some extent. To popularize the raised bed technology among farmers, bed planter should be available to the farmers and the positive benefits should be broadcasted in the mass mediaBangladesh J. Agril. Res. 40(4): 551-566, December 2015